Ex Ante Ethical Perceptions Of Individual Taxpayers Regarding Tax Evasion - Andika Yuliana; Indriyana Puspitosari (Profesional Muda Cendekia Publishing, 2021)
In the theory of planned behavior, a person's perception will determine his attitude. Likewise, one's perception of tax evasion will affect one's compliance in taxation. This study aims to examine the effect of tax fairness, tax culture, love of money and gender on the perception of individual taxpayers on the ethics of tax evasion. This study uses individual taxpayer respondents from KP2KP Sragen, amounting to 80 people. The data analysis technique used is multiple regression analysis. The results show that if tax fairness and tax culture increase, the perception of taxpayers regarding the ethics of tax evasion will decrease. which then encourages individual taxpayers to not comply in carrying out their tax obligations.